Defining SOD1 ALS natural history to guide therapeutic clinical trial design. Issue 2 (3rd June 2016) - Bali, Taha; Self, Wade; Liu, Jingxia; Siddique, Teepu; Wang, Leo H; Bird, Thomas D; Ratti, Elena; Atassi, Nazem; Boylan, Kevin B; Glass, Jonathan D; Maragakis, Nicholas J; Caress, James B; et al.
Abstract : Importance: Understanding the natural history of familial amyotrophic lateral sclerosis (ALS) caused by SOD1 mutations (ALS SOD1 ) will provide key information for optimising clinical trials in this patient population. Objective: To establish an updated natural history of ALS SOD1 . Design, setting and participants: Retrospective cohort study from 15 medical centres in North America evaluated records from 175 patients with ALS with genetically confirmed SOD1 mutations, cared for after the year 2000. Main outcomes and measures: Age of onset, survival, ALS Functional Rating Scale (ALS-FRS) scores and respiratory function were analysed. Patients with the A4V (Ala-Val) SOD1 mutation (SOD1 A4V ), the largest mutation population in North America with an aggressive disease progression, were distinguished from other SOD1 mutation patients (SOD1 non-A4V ) for analysis. Results: Mean age of disease onset was 49.7±12.3 years (mean±SD) for all SOD1 patients, with no statistical significance between SOD1 A4V and SOD1 non-A4V (p=0.72, Kruskal-Wallis). Total SOD1 patient median survival was 2.7 years. Mean disease duration for all SOD1 was 4.6±6.0 and 1.4±0.7 years for SOD1 A4V . SOD1 A4V survival probability (median survival 1.2 years) was significantly decreased compared with SOD1 non-A4V (median survival 6.8 years; p<0.0001, log-rank). A statistically significant increase in ALS-FRS decline in SOD1 A4V compared with SOD1 non-A4V participants (p=0.02) was observed, as well as a statistically significant increase in ALS-forced vital capacity decline in SOD1 A4V compared with SOD1 non-A4V (p=0.02). Conclusions and relevance: SOD1 A4V is an aggressive, but relatively homogeneous form of ALS. These SOD1-specific ALS natural history data will be important for the design and implementation of clinical trials in the ALS SOD1 patient population.